Osteolytic bone lesions – A rare presentation of AML M6. - Geetha N.; Sreelesh KP; Priya Mary Jacob; Lali VS; Rekha A Nair (Mediterranean Journal of Hematology and Infectious Diseases)
Acute myeloid leukemia (AML) M6 is a rare form of AML  accounting  for < 5 % of all AML.  Extramedullary involvement  is very rarely seen in this entity.  Skeletal lesion has not been described in AML M6 before. We discuss the case of  a 17 year old boy with AML M6 who presented with  osteolytic lesion of right humerus.  He was treated with  induction and consolidation chemotherapy. The present case is the first report in literature of AML M6 presenting with skeletal lesions.